Infant neurocognitive development is independent of the use of iodised salt or iodine supplements given during pregnancy - Santiago, Piedad; Velasco, Inés; Muela-Zarzuela, Inés; Sánchez, Baltasar; Martínez, Julia; Rodríguez, Álvaro; Berrio, María; Gutiérrez-Repiso, Carolina; Carreira-Soler, Mónica; Moreno, Alberto; García-Fuentes, Eduardo; Soriguer, Federico (Cambridge University Press, 2013)
The benefits of iodine supplements during pregnancy remain controversial in areas with a mild-to-moderate iodine deficiency. The aim of the present study was to determine the effect of improving iodine intakes, with iodised salt (IS) or iodine supplements, in pregnant Spanish women. A total of 131 pregnant women in their first trimester were randomly assigned to three groups: (1) IS in cooking and at the table, (2) 200 μg potassium iodide (KI)/d or (3) 300 μg KI/d. No differences were found in thyroid-stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3) or thyroid volume (TV) between the three groups. Regardless of the group in which women were included, those who had been taking IS for at least 1 year before becoming pregnant had a significantly lower TV in the third trimester (P= 0·01) and a significantly higher urinary iodine in the first (173·7 (sd 81·8) v. 113·8 (sd 79·6) μg/l, P= 0·001) and third trimesters (206·3 (sd 91·2) v. 160·4 (sd 87·7) μg/l, P= 0·03). Also, no differences were seen in TSH, FT4 or FT3. Children's neurological development was not significantly associated with the consumption of IS for at least 1 year before becoming pregnant and no differences were found according to the treatment group. In conclusion, in pregnant women with insufficient iodine intake, the intake of IS before becoming pregnant was associated with a better maternal thyroid function. The form of iodide intake was not associated with maternal thyroid function or children's neurological development.
Keywords: Embarazo - Complicaciones y secuelas; Iodine; Pregnancy; Thyroid function; Neuropsychomotor development